Kurikulum Pendidikan Agama Kristen yang Kontekstual Bagi Anak Sekolah Minggu Kelas Madya - Talizaro Tafonao; Wiwiet Arie Shanty; Desetina Harefa (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2021)
This paper is a study of the Sunday school curriculum in the church, especially the middle class. Sunday School cannot be separated from the church as a forum for evangelism and teaching about Christian Religious Education. So far, there are still many churches that have not given serious attention to preparing the Sunday School curriculum. Therefore, the purpose of writing this article is to encourage churches and teachers to prepare a curriculum that is in accordance with the characteristics of middle graders. The method used is a library research method, which examines a contextual Christian religious education curriculum for middle class Sunday schools. The analysis process carried out by the author is to use a variety of trusted electronic and library sources to support the author's analysis. The results obtained in this study are the importance of understanding the nature of Sunday school, the characteristics of middle school children, the appropriate Sunday school curriculum and the involvement of Sunday school teachers. Seeing this, the Christian religious education curriculum in middle class is very urgent to be prepared and paid attention to by the church today based on the needs of Sunday school children. Tulisan ini merupakan kajian terhadap kurikulum sekolah minggu di gereja terutama kelas madya. Sekolah Minggu tidak bisa lepas dari gereja sebagai wadah penginjilan dan pengajaran tentang Pendidikan Agama Kristen. Selama ini masih banyak gereja yang belum memberi perhatian serius dalam mempersiapakan kurikulum anak Sekolah Minggu. Oleh karena itu, tujuan penulisan artikel ini adalah mendorong gereja dan guru untuk mempersiapkan kurikulum yang sesuai dengan karakteristik anak kelas madya. Metode digunakan adalah metode penelitian pustaka, yang mengkaji kurikulum pendidikan agama Kristen yang kontekstual bagi sekolah minggu kelas madya. Proses analisis yang dilakukan oleh penulis adalah menggunakan berbagai sumber pustaka maupun elektronik yang terpercaya untuk mendukung analisis. Hasil yang didapatkan dalam kajian ini adalah pentingnya memahami hakikat sekolah minggu, karakteristik anak madya, kurikulum sekolah minggu yang sesuai dan keterlibatan guru sekolah minggu. Dengan melihat hal tersebut maka kurikulum pendidikan agama Kristen di kelas madya merupakan hal yang sangat urgen untuk dipersiapkan dan perhatikan oleh gereja saat ini berdasarkan kebutuhan anak-anak sekolah minggu.